Highly active Pt/In2O3-ZrO2 catalyst for CO2 hydrogenation to methanol with enhanced CO tolerance: The effects of ZrO2 - Sun, Kaihang; Shen, Chenyang; Zou, Rui; Liu, Chang-jun (Applied catalysis. B, Environmental, 2023)
The supported Pt catalyst is normally not active for CO2 hydrogenation to methanol at the presence of CO. Herein, ZrO2 is added into Pt/In2O3 for CO2 hydrogenation to methanol with CO as a co-feed gas. High activity with enhanced CO tolerance is achieved on Pt/In2O3-ZrO2. For example, the space-time yield of methanol reaches 0.569 gmethanol gcat−1 h−1 at 300 °C and 5 MPa under feed gas containing 4% CO of 21,000 cm3·h−1·gcat−1. With the addition of ZrO2, a stronger electron transfer occurs between Pt and the In2O3-ZrO2 solid solution support. This leads to weaker CO adsorption, which suppresses over-reduction of In2O3 and enhances CO tolerance of the Pt catalyst. The oxygen vacancy of In2O3 modified by ZrO2 promotes CO2 activation. The synergy between Zr-modified oxygen vacancy (In-Ov-Zr) and Pt catalyst facilitates methanol synthesis from CO2 hydrogenation via formate route. This is different from Pt/In2O3, which takes CO hydrogenation route. [Display omitted] •ZrO2 significantly changes the electronic structure of Pt/In2O3.•The Pt/In2O3-ZrO2 catalyst possesses high activity with enhanced CO tolerance.•The addition of ZrO2 totally changes the reaction route.•The addition of ZrO2 promotes the activation of hydrogen.•The addition of ZrO2 improves the stability of surface oxygen atoms of In2O3.